Death Penalty in the Lithuanian SSR in 1950–1990: Legal Grounds and Periods - Indrišionis, Darius (Genocidas ir rezistencija, 2016)
The article reviews execution of death row inmates from the Lithuanian SSR between 1950 and 1990. It describes the procedure, the extension of the legal framework governing the enforcement of the death penalty, and the underlying trends.Four periods in the enforcement of the death penalty are discussed: 1) 1950–1952, when the majority of the death row inmates were shot down at the MGB internal prison in Vilnius; 2) 1952–1956, when the death row inmates were transported for execution to Butyrka prison in Moscow; 3) 1956–1969, when executions were carried out in Vilnius (criminals were shot dead in Lukiškių prison and political prisoners were shot dead in the KGB interrogation cell); 4) 1969–1990, when the death row inmates from the Lithuanian SSR profile were executed in the interrogation cell in Minsk (Byelorussian SSR).Between 1950 and 1990, 590 people in one or other way related to the Lithuanian SSR were shot or hanged; this figure includes 116 death row inmates shot in Moscow in 1952–1956, 87 death row inmates shot in Minsk in 1967–1990, 29 death row inmates convicted by Kaliningrad and Kirov courts and executed in Vilnius, and 8 Soviet Army officers sentenced to death and shot in Vilnius.The analysis of the personal stories of inmates and the dynamics of executions show that there was an essential breakthrough about 1956 when the number of political prisoners dropped considerably while the number of criminals started increasing rapidly. This trend allows us to explain a new role of the death penalty in the overall punishment system after 1956, specifically that it predominantly became a tool for combating crime, rather than for annihilating political opponents.
Keywords: Lithuania; Soviet occupation; repressions; death penalty